(untitled) (Research, Society and Development, 2022)
Objective: To analyze the main clinical evidence about the use of hyperbaric oxygen therapy in the treatment of diabetic foot ulcers. Methodology: This is a systematic review carried out using the PRISMA method, in the electronic databases PubMed, Scopus and Web of Science, using the following descriptors: “hyperbaric oxygenation”, “diabetes”, “diabetic foot”, “leg ulcer” and “ischemia” Full texts were included, available in Portuguese, English or Spanish, published between January 2016 and December 2021; studies needed to assess the proportion of people with completely healed diabetic foot ulcers in participants randomized to hyperbaric oxygen therapy and in a control group. Results: 08 articles made up the final sample of this study, with a higher frequency of publication in 2019 (n: 03). All studies used the Randomized Clinical Trial methodology, presenting a strong level of evidence (II). Overall, it was found that the rate of amputation in patients undergoing hyperbaric oxygen therapy was lower compared to the standard treatment established in clinical trials. Three studies reported a reduction in ulcer area and five studies showed that hyperbaric oxygen therapy increased the healing rate of diabetic foot ulcers compared to conventional treatment, with statistically significant results. Conclusion: Current evidence shows some evidence of the effectiveness of hyperbaric oxygen therapy in improving the healing of diabetic foot ulcers. Larger and higher quality clinical trials are needed before the implementation of this therapy in routine clinical practice can be justified.